Aspects of Japan's labor problems / by Miriam S. Farley, with a supplement by W.T.Moran. Issued under the auspices of the International Secretariat, Institute of Pacific Relations - Farley, Miriam S. ; Moran, William T (John Day, 1950)
283 halaman : ilustrasi, tabel ; 20 cm